A highly sensitive breathable fuel cell gas sensor with nanocomposite solid electrolyte. Issue 2 (3rd July 2019) - Zhang, Jing; Jiang, Gaopeng; Cumberland, Timothy; Xu, Pan; Wu, Yalin; Delaat, Stephen; Yu, Aiping; Chen, Zhongwei
Abstract: The present work deals with a poly(vinyl alcohol)‐based membrane mixed with poly(4‐styrenesulfonic acid) to be used as a proton‐conducting solid‐state electrolyte in an electrochemical gas sensor for the detection of alcohol. A cross‐linking bonding semi‐interpenetrating network is formed between the polymer backbones, providing the membrane with superior mechanical property and excellent water retention. Meanwhile, the graphene oxide nanosheets are incorporated into the polymer fibrous backbones, creating impermeable block layers to limit ethanol gas penetration. Importantly, the modification of graphene oxide facilitates the protons transportation in both in‐plane and through‐plane channels of the membrane, boosting excellent conductivities of 0.13 S cm −1 (in‐plane) and 22.6 mS cm −1 (through‐plane) at 75°C, respectively. An alcohol fuel cell sensor assembled with this semi‐interpenetrating network solid electrolyte membrane is fabricated based on direct ethanol fuel cell principle, exhibiting excellent sensitivity, linearity, as well as low ethanol detection limits of 25 ppm. Abstract : A polymer‐based proton‐conducting solid electrolyte with graphene oxide modification is demonstrated on an electrochemical gas sensor. Superior in‐plane and through‐plane conductivities and sensitive detection to low limit ethanol vapor approve its promising application in an alcohol fuel cell sensor.